Menstruation-related disseminated intravascular coagulation in an adenomyosis patient: case report and review of the literature. - Cernogoraz, Alice; Schiraldi, Luigi; Bonazza, Deborah; Ricci, Giuseppe (Gynecol Endocrinol, 2019)
Disseminated intravascular coagulation (DIC) is a high mortality coagulopathy that leads to simultaneous thrombotic and bleeding problems. It occurs as a complication in different disease as malignancies, obstetrical catastrophes, bacterial sepsis and traumas. We report on an extremely rare case of acute DIC in a patient with misdiagnosed adenomyosis and massive methrorragia which led to acute kidney failure. The patient was successfully treated with hysterectomy and blood product transfusions; however, a slight reduction of renal function persisted. We were able to confirm the cause-consequence link between adenomyosis and consumptive DIC since we saw the thrombi in the adenomyotic uterus from early hysterectomy specimen. Moreover, this is the first case, for the best of our knowledge, in which systemic consequences persist in an adenomyosis patient who developed a DIC. Early diagnose and treatment of acute DIC is essential for patient's survival and to prevent severe complications: adenomyosis should be kept in mind as a possible cause of DIC when a patient shows up with massive bleeding.